Modeling Complex Systems - Boccara, Nino.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Modeling Complex Systems, 2nd Edition, explores the process of modeling complex systems, providing examples from such diverse fields as ecology, epidemiology, sociology, seismology, and economics. It illustrates how models of complex systems are built and provides indispensable mathematical tools for studying their dynamics. This vital introductory text is useful for advanced undergraduate students in various scientific disciplines, and serves as an important reference book for graduate students and young researchers. This enhanced second edition includes: . -recent research results and bibliographic references -extra footnotes which provide biographical information on cited scientists who have made significant contributions to the field -new and improved worked-out examples to aid a student$1 (Bs comprehension of the content -exercises to challenge the reader and complement the material Nino Boccara is also the author of Essentials of Mathematica: With Applications to Mathematics and Physics (Springer, 2007).s
How to Build Up a Model -- Differential Equations -- Recurrence Equations -- Chaos -- Spatial Models -- Networks -- Power-Law Distributions.
Keywords: Physics; Ecology; Systems theory; Computer science; Physics; Statistical Physics, Dynamical Systems and Complexity; Numerical and Computational Physics; Computational Science and Engineering; Mathematical Modeling and Industrial Mathematics; Theoretical Ecology/Statistics.; Systems Theory, Control